Innovation Strategies of Three of the BRICS: Brazil, India and China - What can we learn from Three Different Approaches? - Dahlman, C (SLPTMD (Department of International Development, University of Oxford), 2008)
Innovation in developing countries should not be defined just in terms of shifting global frontier technology but in terms what is new to the country. Innovation strategy should include policies and mechanisms that affect a country’s ability to draw on global knowledge as well as domestic R&D; effort. Such strategy will be affected by policies that include trade, foreign investment, technology transfer, domestic R&D;, human capital and education more generally. From this broad perspective, the innovation strategies of Brazil, China and India—the three largest developing economies - have been quite different. India has been the most autarkic until recently. China has drawn the most on global knowledge, although more recently it is investing massively in it own R&D.; Brazil is somewhat in between. It has been almost as closed as India to trade, but more open that India in terms of FDI. Moreover, Brazil is falling behind both countries in domestic R&D; effort. The three countries have also had very different growth performance over the last 25 years. This paper examines the innovation strategies of the three countries, compares their economic performance over the last 25 years, and draws some implications about the link between innovation strategy and economic performance.